Effect of extraction methods and sulfiting on qualities of "kalamansi" (Citrus microcarpa bunge) juice stored at accelerated temperature - Abarquez, Ma. Proserpina C.
ABSTRACT "Kalamansi" juice, extracted by pulping and hand-reaming methods, was studied for its quality factors. Its keeping quality as affected by SO2 levels while stored at 55C and at room temperature (78-86F) was determined based on some parameters, namely: a) color b) pH c) solube solids (S.S.) as degree Brix (B) d) titrable acidity (T.A.) e) viscosity f) vacuum g)microbiological and h) sensory evaluation. After extraction, "kalamansi" juice was pasteurized and subsequently treated with 2 levels of SO2. Samples were then stored at 55C for 3 weeks and at room temperature for 1 month after hot-packing and sealing. Statistically significant experimental results revealed that for both objective and sensory tests, pulped samples showed a tendency to be less acidic than the hand-reamed. The former also indicated an inverse relationship of their T.A. and S.S. values, a better color retention and high viscosity relative to the hand-reamed with increasing storage at both temperatures. As expected, the sulfites appeared to exert no significant change on the juice quality such as its: pH, T.A., S.S. and viscosity values. However, detectable bleaching effect which increased with time of storage was shown by the sulfited samples. Changes occurring in the samples stored at 55C appeared to have gone at a much faster rate than those stored at room temperature with probably a week's storage at 55C being equivalent to more than a month's storage at room temperature.